Adverse Childhood Experiences and Alcohol Consumption in Midlife and Early Old-Age. (9th November 2015) - Leung, Jessica Pui Kei; Britton, Annie; Bell, Steven
Abstract : Aims: To examine the individual and cumulative effects of adverse childhood experiences (ACEs) on alcohol consumption in midlife and early old-age, and the role of ACEs in 10-year drinking trajectories across midlife. Methods: Data were from the Whitehall II study, a longitudinal British civil service-based cohort study ( N = 7870, 69.5% male). Multinomial logistic regression was used to examine the individual and cumulative effects of ACEs on weekly alcohol consumption. Mixed-effect multilevel modelling was used to explore the relationship between ACEs and change in alcohol consumption longitudinally. Results: Participants who were exposed to parental arguments/fights in childhood were 1.24 (95% CI 1.06, 1.45) times more likely to drink at hazardous levels in midlife (mean age 56 years) after controlling for covariates and other ACEs. For each additional exposure to an ACE, the risk of hazardous drinking versus moderate drinking was increased by 1.12 (95% CI 1.03, 1.21) after adjusting for sex, age, adult socio-economic status, ethnicity and marital status. No associations between ACEs and increased risk of hazardous drinking in early old-age (mean age 66 years) were found. In longitudinal analyses, ACEs did not significantly influence 10-year drinking trajectories across midlife. Conclusion: The effect of exposure to parental arguments on hazardous drinking persists into midlife.